Progression of liver fibrosis in HIV/hepatitis C virus‐coinfected individuals on antiretroviral therapy with early stages of liver fibrosis at baseline. Issue 4 (19th November 2013) - Sanmartín, R; Tor, J; Sanvisens, A; López, JJ; Jou, A; Muga, R; Ojanguren, I; Barluenga, E; Videla, S; Planas, R; Clotet, B; Tural, C
<x xml:space="preserve">Abstract</x> Objectives The aim of the study was to assess the progression of liver fibrosis in HIV/hepatitis C virus (HCV)‐coinfected patients with no or mild‐to‐moderate fibrosis (stages F0−F2). Methods Liver fibrosis was reassessed by transient elastometry (TE) between January 2009 and November 2011 in HIV/HCV‐coinfected patients with stage F0−F2 fibrosis in a liver biopsy performed between January 1997 and December 2007. Patients with liver stiffness at the end of follow‐up < 7.1 kPa were defined as nonprogressors, and those with values ≥ 9.5 kPa or who died from liver disease were defined as progressors. Cirrhosis was defined as a cut‐off of 14.6 kPa. The follow‐up period was the time between liver biopsy and TE. Cox regression models adjusted for age, gender and liver fibrosis stage at baseline were applied. Results The median follow‐up time was 7.8 years [interquartile range (IQR) 5.5–10 years]. The study population comprised 162 patients [115 (71%) nonprogressors and 47 (29%) progressors; 19 patients (11.7%) had cirrhosis]. The median time from the diagnosis of HCV infection to the end of follow‐up was 20 years (IQR 16.3–23.1 years). Three progressors died from liver disease (1.8%). The variables associated with a lower risk of progression were age ≤ 38 years (hazard ratio (HR) 0.32; 95% confidence interval (CI) 0.16–0.62; P = 0.001], having received interferon (HR 2.18; 95% CI 1.14–4.15; P = 0.017), being hepatitis B virus surface antigen (HBsAg) negative (HR 0.20; 95% CI 0.04–0.92; P = 0.039), and baseline F0−F1 (HR 0.43; 95% CI 0.28–0.86; P = 0.017). Conclusions A high proportion of patients with stage F0−F2 fibrosis progress to advanced liver fibrosis. Advanced liver fibrosis must be included in the list of diseases associated with aging. Our results support the recommendation to offer HCV antiviral therapy to HIV/HCV‐coinfected patients at early stages of liver fibrosis.